Geographic location of the patronymic toponyms ending in -ice and ethnic boundaries - Czapla, Anna (Geographical names in physical space, 2016)
The patronymic toponyms ending in -ice are the most productive in the Polish regions of Małopolska (Little Poland), Śląsk (Silesia) and Wielkopolska (Great Poland). These formations are relatively infrequent in the other two regions: Mazowsze (Mazovia) and Pomorze (Pomerania). The toponyms in question are not an exclusively Polish onomastic phenomenon. They are to be easily found in the other Slavic territories: in Czech Republic, Moravia, the countries of former Yugoslavia and in the Germanized west Lechitic and Lusatian territories. They are rather infrequent in the Ukraine and in some parts of Belarus. Do all these facts allow to make a general conclusion concerning the tribal borderline between the East and West Slavic zones? The facts we analyse have been used to defend the radical opnion taken by J. Nalepa, who claims of the originally Polish nature of the broadly understood region of Przemyśl, or by O. A. Kupczyński, who claims that the East- West Slavic tribal borderline ran along the rivers Wisłok, lower San, Wieprz and Bug. W. Makarski claims that the fact of the geographical distribution of toponyms in -ice cannot decidedly answer the question about the tribal borderline, since genetically, the nature of the -ice formations is identical in all the regions, and an attempt to situate this onomastic problem in the tribal era raises serious objections. The distributional analysis of the patronymic toponyms in -ice in contemporary Poland and those in the territories of former Polish states reveals a close relationship between the accumulation of these toponyms with land quality, which is an obvious fact. One can observe a gradual decrease in the number of the -ice formations when moving from the West to the East of Poland. Exceptional in this respect is their relative accumulation in the South-Eastern Poland. They are frequent in the districts of Przemyśl, Jarosław, Moscice, Gródek Jagielloński, Stary Sambor, Sambor and Drohobycz, but they are not well represented in the districts of Łańcut or Rzeszów. Very few -ice toponyms are to be found in the region of Sanok, neighbouring the region of Przemyśl. All these facts make it hardly tenable to put forward any claims concerning ethnic borderlines. All that can be observed is the lack of link between the toponyms under analysis and the corresponding ones from the Little Poland.